PERAN KEPEMIMPINAN DALAM MENINGKATKAN KINERJA ANGGOTA ORGANISASI - Lidya Rosnoviana; Muhammad Irwan Padli Nasution (CV. Barokah Publsiher, 2025)
Leadership is a crucial factor in determining the direction and success of an organization. A leader’s role is not only to issue orders but also to serve as a role model and motivator for their members. This article aims to understand how leadership can influence the performance of organizational members. This paper uses a literature review method by collecting and analyzing various relevant literature on leadership theory and organizational performance. The study results indicate that effective leadership can increase work enthusiasm, responsibility, and cooperation among members. Leaders who possess good communication skills and are able to provide motivation can create a conducive and productive work environment. Thus, good leadership is a key to improving performance and achieving optimal organizational performance.